Kategori Perkawinan Belum Tercatat dalam Blangko Kartu Keluarga Perspektif Yuridis - Aljarofi, Amanda Zubaidah (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
This article discusses marital status in a family card that has a registered marriage and an unregistered marriage. The important question to be answered through this article is that the legal basis for making the marriage category has not been recorded as one of the marital status in the family card blank. The analysis is carried out using the applicable laws and regulations namely Law Number 1 of 1974 concerning Marriage, Government Regulation Number 9 of 1975 concerning Implementation of Law Number 1 of 1974 concerning Marriage, Compilation of Islamic Law, and Regulation of the Minister of Religion of the Republic of Indonesia Number 19 of 2018 concerning Marriage Registration. Changes in marital status in family card blanks regulated in Minister of Domestic Affairs Regulation Number 118 of 2017 concerning Family Card Blanks, Registration and Quotation of Civil Registration Deed, caused the Directorate General of Population and Civil Registration of the Ministry of Home Affairs of Indonesia to make the development of the population database change to SIAK 7. This change has caused the registration of marriages which initially functioned to guarantee legal order as instruments of legal certainty through proof of marriages, to be disorderly in the law. It is because in the long-term marriages have not been recorded and remain facilitated by the state through fulfillment of administrative rights. [Artikel ini membahas status perkawinan dalam kartu keluarga yang tertulis kawin tercatat dan kawin belum tercatat. Pertanyaan penting yang ingin dijawab melalui artikel ini adalah dasar hukum dijadikannya kategori perkawinan belum tercatat sebagai salah satu status perkawinan dalam blangko kartu keluarga dan dijadikannya kategori perkawinan belum tercatat sebagai salah satu status perkawinan dalam blangko kartu keluarga. Analisis dilakukan dengan menggunakan peraturan perundang-undangan yang berlaku yakni UU Nomor 1 Tahun 1974 Tentang Perkawinan, Peraturan Pemerintah Nomor 9 tahun 1975 tentang Pelaksanaan UndangUndang Nomor 1 Tahun 1974 Tentang Perkawinan, Kompilasi Hukum Islam, dan Peraturan Menteri Agama Republik Indonesia Nomor 19 Tahun 2018 Tentang Pencatatan Perkawinan. Perubahan status perkawinan dalam blangko kartu keluarga yang diatur dalam Peraturan Menteri Dalam Negeri Nomor 118 Tahun 2017 Tentang Blangko Kartu Keluarga, Registrasi dan Kutipan Akta Pencatatan Sipil menyebabkan Direktorat Jenderal Kependudukan dan Pencatatan Sipil Kementerian Dalam Negeri Indonesia membuat pengembangan database kependudukan berganti menjadi SIAK 7. Perubahan tersebut menyebabkan kedudukan pencatatan perkawinan yang semula berfungsi untuk menjamin ketertiban hukum (legal order) sebagai instrumen kepastian hukum melalui alat bukti perkawinan, menjadi tidak tertib hukum karena dalam jangka panjang perkawinan belum tercatat tetap difasilitasi negara melalui pemenuhan hak administratif kependudukan.]